Bryant & Dethloff, A History of American Business - Tedesco, Paul (Teaching History: A Journal of Methods, 1991)
I reviewed the earlier first edition of C. Joseph Pusateri's A History of American Business in this journal in 1985 (Spring, x, 1). At that time I chose to review, in addition, all the other basic texts that had appeared in response to a growing interest in American business history. One of those was the first edition of Bryant and Dethloff's A History of American Business, published in 1983, and which I had used in my own upper-level undergraduate/graduate course in American business history. At that time I wrote that "this text (the first edition) is much better for undergraduate use, but breaks from the chronological tradition to follow a topical outline." On the whole, I felt, and still do, that students experienced some difficulties following the text if, as I do, the instructor utilizes a shorter chronological approach interspersed with cases. I believed then, and I do now, that unless the instructor takes care, the student will not see the constant interplay of business and society over time. That fact is supported by the catchy title . .. rather it would have been "business in American history" or "American business history."